PERAN GURU DALAM PELAKSANAAN PROGRAM HOME VISIT DALAM UPAYA PEMBINAAN SISWA DI SD IT AL HIJRAH 2 DELI SERDANG - Khalisatun Husna; Budi Budi (STKIP Pesisir Selatan, 2026)
Limited communication between schools and parents often becomes an obstacle in optimizing student development. This study aims to analyze the role of teachers in implementing the home visit program and its impact on student development at SD IT Al Hijrah 2 Deli Serdang. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, while data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The findings indicate that teachers play comprehensive roles in the implementation of the home visit program, including as connectors, observers, guides, motivators, problem solvers, and evaluators. The home visit program has proven to have a positive impact on student development, both academically and non-academically, such as improving learning motivation, discipline, responsibility, and character building. In addition, the program enhances parental involvement and strengthens the relationship between schools and families. These findings confirm that home visit is an effective strategy for holistic student development through the integration of teacher and parent roles. This study implies the importance of strengthening collaboration between schools and families to support sustainable student development.